La sepoltura dei musulmani in contesto non islamico fra teoria e prassi - De Angelo, Carlo (Annali di Ca’ Foscari: Serie Orientale, 2025)
This article is a response to the invitation of the Union of Italian Islamic Communities to the academic world to pay more attention to the issue of Islamic burial and cemetery spaces in Italy. It has two objectives. The first is to identify and analyse Islamic rules on burial in a non-Islamic context in order to verify their compatibility with Italian legislation. The second objective is to carry out an initial mapping of the existing Islamic cemeteries in Campania, the actual number of which is one of the data on the basis of which it will be possible to determine whether and to what extent the right of Muslims living in the area to be buried in accordance with Islamic rules is respected.